Estudo dos coeficientes da curva de adensamento para um solo superficial de Pau dos Ferros/RN - Gomes, Leonardo Sucupira (Universidade Federal Rural do Semi-Árido, 2019)
Foundations poorly designed to lack or inefficiency in subsurface studies can lead to the emergence of cracks and other soil pathologies that directly affect these kind of structures, compromising their stabilization and, in some cases, may establish great high risk of tipping. One of the phenomena that can occur, where it happens the expulsion of water or air from its voids, causing particles to deform, and consequently what is called elastic repression or primary soil compaction. Thus, having knowledge of geotechnical techniques is a way to prevent these events from happening and allow the soil layer to work in order to maintain its resistance and its state of load support. Based on this, the present work refers to the analysis of an undeformed soil sample, verifying its properties and characteristics, classifying and characterizing this soil according to the laboratory tests, also determining its physical indices and the results of densification coefficients. The next step was the testing and analysis of this soil to obtain the results. Thus, results were obtained showed divergences from the results obtained by the empirical methods, this is due to the heterogeneity of the soil, which has different shapes and characteristics because of the place from which the studied sample was collected. The density curve coefficients found were Cc = 0.115836, Cr = 0.006993 and Ce = 0.01661, proving the differences in relation to the results of the empirical equations were due to the place where they were performed and the obtainment of coefficients of compression and recompression of the soil under study in this work from the place where the sample was extracted.
Keywords: Amostra indeformada; Recalque; índices físicos; Undeformed sample; Repression; Physical indices; ENGENHARIAS::ENGENHARIA CIVIL